Pengaruh Earning Per Share, Debt To Equity Ratio Dan Net Profit Margin Terhadap Harga Saham Pada Industri Sub Sektor Perkebunan Yang Terdaftar Di BEI Periode 2013-2017 - Maga Syawal Husein Lubis (Science of Management and Students Research Journal (SMS), 2019)
The purpose of this study was to find out and analyze the effect of Earning Per Share, Debt to Equity Ratio and Net Profit Margin on stock prices simultaneaously and partially to the company on the IDX for the 2013-2017 period. This is a type of research method that is quantitative data based on secondary data. Secondary data sources can be internet, references books,related research journals.the analysis used the classic assumtion test (normality test ,multicolourity test,heterokedacity test, autocorrelation test), hypothesis testing (f test, t test), multiple linear analysis, test of the determination coefficient R square. All research data were processed using SPSS version 20. The object in this study is the plantation sector companies listed on the indonesia Stock Exchange in the period 2013-2017. Sampling uses criteria that have been described previously, after passing the criteria the number selected as a sample of 5 compenies. Based on predetermined criteria. obtained a list of companies that meet the sample criteria in this study Astra Agro Lestari Tbk, Tunas Baru Lampung Tbk, PP London Sumatera Indonesia Tbk, Sampoerna Agro Tbk, Salim Ivomas Pratama Tbk.  The results of this study Simultaneously the fount is 154.449 with a probability of 0.000 smaller than 0.05 so that it can be concluded that all independent variables (EPS, DER, NPM) together have a significant effect on stock prices. Changes that occur in stock prices can be explained by the variable EPS, DER, NPM amouting to 3.59%, the reamining 96.41% is explained by other variables outsided the model. The conclusion of this study the partially variable Earning Per Share has a significant effect on stock prices with a coefificient of 19.809 and a significance of 0.000. the result obtained show Earning Per Share has a significant positive effect on stock prices. Variable Debt To Equity Ratio has no significant effect on stock prices with a coefficient of 3.338 and a significant of 0.003. the variable Net Profit Margin has no signifficant effect on stock prices with a coefficient of 4.916 and a significance of 0.000.